RANCANG BANGUN APLIKASI PENGADAAN BARANG DISTRIBUSI PADA PT FAMOUS CHICKEN DENGAN MENGGUNAKAN METODE DISTRIBUTOR REQUIREMENT PLANNING (DRP) - teguh pradana; Muhamad Fani Rifqi; Renita Selviana (LPPM ITB Yadika Pasuruan, 2022)
The need for fast, precise and accurate information is absolute in this fast-paced era. The delay in presenting the required information will cause the information to become irrelevant for its users. Thus, a good system must be able to provide timely information, with accurate and precise data in the processing process.Goods Distribution Information System Through Transporter at PT Super Famous Chicken departs from the company's vision, mission and goals. Namely to be a Goods Distribution Information System through a Transporter at PT Super Famous Chicken that has quality in providing services to the community. Various ways to improve the quality of goods distribution services have been taken, among others by applying the distribution data archiving method which will conduct further studies more efficiently, simplify the transaction data processing, improve the overall quality of resources, and improve the company's accreditation status.This information system will further simplify the processes mentioned above by utilizing data communication network information technology. So that the processing of existing data will be faster and more accurate, and eliminate duplication of data that arises between existing sections.